An analysis of graduate students’ perceptions of civic engagement in higher education in Côte d’Ivoire - Assoman, N'zoret Innocent (Kansas State University, 2024)
This study explores the perceptions of civic engagement among graduate students in the Ivorian higher education system, utilizing Critical Participatory Action Research (CPAR) as the methodological framework. The study identifies key themes through qualitative analysis, shedding light on the challenges and opportunities within the institutional landscape. There is substantial literature (Jacoby, 2009; Prentice, 2011) that demonstrate the important role of higher education in preparing students to become civically engaged citizens for their nations. However, in the Ivorian context findings reveal a traditional management structure, limited administrative support towards students’ engagement, and varied student initiatives across disciplines. Recommendations include empowering administrative leadership, amplifying student voices, and establishing interdisciplinary civic engagement programs and clubs across universities. My future research agenda involves translating key chapters for broader accessibility, engaging in action-oriented collaboration, and contributing to global conversations on civic engagement. The study seeks to enrich the scholarly discourse and promote positive change within the Ivorian higher education system and beyond. The study reveals a strength of CPAR inquiry for this research in the Ivorian context as a tool in facilitating mindset change. By employing CPAR, participants accustomed to an environment where leadership is often associated with hierarchical structures and positions were able to embrace a collaborative mindset. This shift enabled them to recognize the collective power they possess to effect social change.
Keywords: Civic engagement; Social change leadership; Critical participatory action research; Higher education; Collaboration; Côte d'Ivoire